Serum Uric Acid Might Be Positively Associated With Hypertension in Chinese Adults: An Analysis of the China Health and Nutrition Survey - Han, Yingdong; Han, Kaidi; Han, Xinxin; Yin, Yue; Di, Hong; Wu, Juan; Zhang, Yun; Zeng, Xuejun (Frontiers in Medicine, 2022)
Background: Previous studies have clarified the relationship between serum uric acid (SUA) and hypertension; most of previous studies suggest that elevated uric acid levels are associated with an increased risk of hypertension, while in China, there are relatively few studies to explore above association. The objective of this longitudinal study is to investigate the correlation of SUA and hypertension in Chinese adults with a nationwide large-scale sample. Methods: Data from the China Health and Nutrition Survey 2009, 2011, and 2016 were used; a total of 8,469 participants (3,973 men and 4,496 women) were involved. This study was conducted separately by gender. Clinical characteristics of the participants among different uric acid groups are compared. The binary logistic regression analysis was conducted to examine the association between SUA and hypertension. Restricted cubic spline analysis with three knots of the SUA concentration were used to characterize the dose-response relationship. Additionally, we compared the incidence of hypertension in the different baseline uric acid groups during follow-up in 2011 and 2015. Results: After the covariates were fully adjusted, we found that elevated uric acid levels were correlated with increased risk of hypertension in both males (p < 0.01) and females (p < 0.01). With 2-year or 6-year of follow-up, we found participants with higher baseline uric acid levels had a higher incidence of hypertension (p < 0.01). In stratified analysis by obesity, above relationship remained significant in nonobesity population (males: p < 0.05, females: p < 0.01) and became nonsignificant in obesity people. In stratified analysis by age, above positively correlation remained significant in middle-aged men (p < 0.05) and elderly women (p < 0.01). Restricted cubic spline revealed the dose-response relationship between SUA and hypertension; we also found that above relationship was much stronger in females. Conclusion: This study suggests that elevated SUA levels might be positively associated with an increased risk of hypertension in general Chinese adults.